2006
DOI: 10.1029/2005jd006691
|View full text |Cite
|
Sign up to set email alerts
|

Ability of the land surface model ISBA‐A‐gs to simulate leaf area index at the global scale: Comparison with satellites products

Abstract: [1] The land surface model (LSM) ISBA-A-gs (Interactions between Soil, Biosphere and Atmosphere, CO 2 -reactive) is specifically designed to simulate leaf stomatal conductance and leaf area index (LAI) in response to climate, soil properties, and atmospheric carbon dioxide concentration. The model is run at the global scale, forced by the GSWP-2 meteorological data at a resolution of 1°for the period of 1986-1995. We test the model by comparing the simulated LAI values against three satellite-derived data sets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
195
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(198 citation statements)
references
References 71 publications
2
195
0
1
Order By: Relevance
“…Over savannah, they are in phase with MODIS whereas CYCLOPES shows a LAI peak one month earlier. This delay between CTESSEL and the satellite products has also been observed by Gibelin et al [2006] who evaluate ISBA-a-gs (from which the photosynthesis and growth modules are taken) at the global scale. The decrease of LAI after the end of the rainy season is quicker for CYCLOPES than for MODIS.…”
Section: Ctessel Against the Satellite-derived Lai And Bias Correctionmentioning
confidence: 90%
See 1 more Smart Citation
“…Over savannah, they are in phase with MODIS whereas CYCLOPES shows a LAI peak one month earlier. This delay between CTESSEL and the satellite products has also been observed by Gibelin et al [2006] who evaluate ISBA-a-gs (from which the photosynthesis and growth modules are taken) at the global scale. The decrease of LAI after the end of the rainy season is quicker for CYCLOPES than for MODIS.…”
Section: Ctessel Against the Satellite-derived Lai And Bias Correctionmentioning
confidence: 90%
“…The photosynthesis parameters of the A-gs module (g c , N a , e, f, etc. ; see Appendix A) are taken from Gibelin et al [2006] who describe the implementation at the global scale of ISBA-A-gs and validate the global simulation from satellite observations. In addition, ECOCLIMAP provides with a climatology of monthly Leaf Area Index that can be used to forced the LAI in CTESSEL by shunting the growth module.…”
Section: Global Net Ecosystem Exchange Data Sets: Sib and Casamentioning
confidence: 99%
“…ISBA-A-gs calculates interactively the leaf biomass and the LAI, using a simple growth model (Calvet et al, 1998). Gibelin et al (2006) and Brut et al (2009) showed that ISBA-A-gs provides reasonable LAI values at regional and global scale under various environmental conditions. The ecosystem respiration (Reco) is described in the model as a basal rate modulated as a function of soil moisture and soil temperature (Albergel et al, 2010b).…”
Section: The Isba-a-gs Model Within Surfexmentioning
confidence: 99%
“…A typical seasonal cycle simulated by ORCHIDEE presents (1) a dormancy phase, (2) a sharp increase of LAI over a few days at the leaf onset, (3) a more gradual growth governed by photosynthesis, until a maximum LAI value has been reached, (4) stable maximum LAI values until the senescence date has been reached, (5) a senescence phase presenting an exponential decline of LAI. The ISBA-A-gs growth model currently used in the SURFEX modelling platform (http://www.cnrm.meteo.fr/surfex/) is described in Gibelin et al (2006). No specific phenology model is used, as the vegetation growth and senescence are entirely driven by photosynthesis.…”
Section: Main Differences Between Isba-a-gs and Orchideementioning
confidence: 99%
See 1 more Smart Citation